The Structure and Activity of Double-Nitroimidazoles. A Mini-Review - Justyna Żwawiak; Lucjusz Zaprutko (Scientia Pharmaceutica, 2018)
Many interesting applications have been found for nitroimidazoles as therapeutic agents. Among others, some of these compounds can radiosensitize hypoxic tumor cells. The introduction of a second nitroimidazole ring to the molecule can improve the level of its pharmacological effect. The aim of this article is to overview the literature concerning active compounds that contain two nitroimidazole moieties in their structures.